Effect of mental fatigue on performance, perceptual and physiological responses in orienteering athletes - Batista, M. M.; Paludo, A. C.; da Silva, M. P.; Martins, M. V.; Pauli, P. H.; Dal'maz, G.; Stefanello, J. M.; Tartaruga, M. P. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Mental fatigue seems to impair the athletes` performance; however, in sports with high cognitive demand, such as orienteering, this negative effect could be attenuated during the race. Therefore, this study investigated mental fatigue effect on performance, perceptual, and physiological responses in orienteers. METHODS: Fifteen male orienteers (30±8 years) participated in the study. Two conditions of cognitive tasks preceded the orienteering performance, performed randomly: 30 minutes of mental exertion (experimental condition [EXP]) by Stroop task, or 30 min without mental exertion (control condition [CON]). Orienteering performance was determined by the time required to perform the Orienteering race. The perceived recovery and motivation were evaluated in each condition, pre-cognitive task, and heart rate during the task. Perceived exertion (RPE) was measured pre- and post-orienteering race. Orienteering performance and perceived performance were measured immediately after the race. RESULTS: Orienteering performance and remain variables showed no significant differences between conditions (EXP versus CON) (P>0.05). Although a slight increase in performance-time was found in EXP (40.8±11.4 min) versus CON (38.4±13 min) (P=0.4; ES=0.20). RPE increase post-EXP (P<0.05; ES=0.96) but not post-orienteering race (P>0.05). CONCLUSIONS: Thirty minutes of the cognitive task did not significantly affect the perceptual and physiological responses but demonstrates the addition of 2.4 minutes to orienteering performance. Orienteers may cope with mental effort due to the cognitive demands and physical conditions required in orienteering.